Investigating fibroblast cells under "safe" and "injurious" blue‐light exposure by holographic microscopy. Issue 6 (18th April 2016) - Calabuig, Alejandro; Mugnano, Martina; Miccio, Lisa; Grilli, Simonetta; Ferraro, Pietro
Abstract : The exposure to visible light has been shown to exert various biological effects, such as erythema and retinal degeneration. However, the phototoxicity mechanisms in living cells are still not well understood. Here we report a study on the temporal evolution of cell morphology and volume during blue light exposure. Blue laser irradiation is switched during the operation of a digital holography (DH) microscope between what we call here "safe" and "injurious" exposure (SE & IE). The results reveal a behaviour that is typical of necrotic cells, with early swelling and successive leakage of the intracellular liquids when the laser is set in the "injurious" operation. In the phototoxicity investigation reported here the light dose modulation is performed through the very same laser light source adopted for monitoring the cell's behaviour by digital holographic microscope. We believe the approach may open the route to a deep investigation of light‐cell interactions, with information about death pathways and threshold conditions between healthy and damaged cells when subjected to light‐exposure.3D Morphology and quantitative phase information from late stage of necrosis cell death. Abstract : A study on the temporal evolution of cell morphology and volume during blue light exposure is reported. The results reveal a behaviour that is typical of necrotic cells, with early swelling and successive leakage of the intracellular liquids when the laser is set in the "injurious" operation. The approach may open the route to a deep investigation of light‐cell interactions, with information about death pathways and threshold conditions between healthy and damaged cells when subjected to light‐exposure.